Looking beyond loss and damage: Reframing insurance to promote adaptation and resilience - Kramer, Berber; Hellin, Jonathan; Hansen, James; Rose, Alison; Braun, Mélody (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
In much of the developing world, climate change is expected to increase the risk from extreme weather events, and scaling insurance is vital to enhance agricultural risk management and adaptation among the rural poor. Insurance program impacts however too often claim impacts based on the number of farmers insured, or total payouts made; instead of documenting livelihood impacts, and/or addressing key challenges that hamper impacts on resilience. A mix of stakeholder expertise is required to design, evaluate and scale insurance programs that have the potential to enhance resilience among the rural poor. We highlight the contribution that agricultural research-for-development (AR4D) can play to help strengthening scaling efforts and evaluating the impacts of insurance on resilience.